Geometric verification for Saimaa ringed seal re-identification - Immonen, Veikka (2023)
Ongoing conservation efforts of the Saimaa ringed seal (Pusa hispida saimensis) utilize an image-based re-identification, but the re-identification is mostly done manually. Due to enlarging image data sets of seals, the identification process is getting more time-consuming, increasing the demand for automated alternatives. NOvel Ringed seal Re-identification by Pelage Pattern Aggregation (NORPPA) is a method proposed to automatically re-identify seal individuals. The method utilizes the permanent and unique pelage pattern of seals by extracting and aggregating the features of the pelage pattern. However, the method does not utilize spatial and geometric information about the features which may cause false identifications. In this thesis, a geometric verification method called Geometric Verification Algorithm (GVA) is developed for the latest version of NORPPA. The method utilizes spatial information of the pelage pattern and tries to re-evaluate the re-identification results of NORPPA taking geometric consistency of pattern features into account. All experiments showed that the addition of GVA improved the re-identification accuracy of NORPPA. Tämänhetkiset saimaannorppien (Pusa hispida saimensis) suojelutoimenpiteet hyödyntävät norppayksilöiden tunnistamista riistakamerakuvista. Tunnistus tehdään vielä pääosin manuaalisesti ja mikä on raskas prosessi. Riistakameradatan määrän kasvaessa kysyntä automaattisille tunnistusmenetelmille on myös kasvanut. NORPPA on yksi saimaannorppien tunnistusalgoritmi. Algoritmi hyödyntää norpalle ominaista rengaskuvioista turkkia. Algorimi yrittää tunnistaa saimaannorpan erottelemalla ja aggregoimalla kylkikuviosta tyypillisiä ominaispiirteitä. Algoritmi ei kuitenkaan ota tunnistettujen ominaispiirteiden sijaintia valokuvassa lainkaan huomioon, joka saattaa aiheuttaa virheellisiä tunnistuksia. Kandidaatintyössä kehitettiin NORPPA-algoritmiin geometrista yhtäpitävyyttä mittaava lisäosa: Geometric Verification Algorithm (GVA). GVA hyödyntää kylkikuviosta tunnistettujen ...